Developmental toxicity and neurotoxicity of penconazole enantiomers exposure on zebrafish (Danio rerio). (December 2020) - Jia, Ming; Teng, Miaomiao; Tian, Sinuo; Yan, Jin; Meng, Zhiyuan; Yan, Sen; Li, Ruisheng; Zhou, Zhiqiang; Zhu, Wentao
Abstract: Penconazole is a widely used chiral triazole bactericide that may adversely affect the environment. It contains two corresponding enantiomers and there may be differences in toxicity between the isomers. Therefore, in this study, we exposed zebrafish embryos to different concentrations of the penconazole enantiomer to study the developmental toxicity and neurotoxicity of penconazole on zebrafish and the difference in toxicity between enantiomers. The results showed that penconazole exposure caused adverse effects on zebrafish embryos, such as autonomous motor abnormalities, heart rate slowing, and increased deformity, resulting in significant developmental toxicity. Meanwhile, also caused the zebrafish larvae to slow movement, the neurotransmitter content and nervous system related gene expression significantly changed, which proved that penconazole also caused neurotoxicity to zebrafish. Interestingly, our results also clearly show that (+)-penconazole is significantly more toxic to zebrafish than (−)-penconazole at the same concentration, whether it is developmental toxicity or neurotoxicity, which suggests that we should focus on (+)-penconazole more when conducting toxicological studies on penconazole. Graphical abstract: Image 1 Highlights: Penconazole has developmental toxicity and neurotoxicity to zebrafish. The toxicity of penconazole to zebrafish is dose-dependent. The toxic effects of (+)-penconazole are higher than (−)-penconazole to zebrafish. Abstract : Penconazole exposure causes developmental toxicity and neurotoxicity in zebrafish with dose-dependent; meanwhile, the toxic effects of (+)-penconazole are higher than (−)-penconazole.